Minimally invasive surgery for unilateral Wilms tumors: Multicenter retrospective analysis of 50 transperitoneal laparoscopic total nephrectomies. Issue 5 (16th February 2020) - Bouty, Aurore; Blanc, Thomas; Leclair, Marc David; Lavrand, Frederic; Faure, Alice; Binet, Aurelien; Rod, Julien; O'Brien, Mike; Sarnacki, Sabine; Nightingale, Michael; Heloury, Yves; Varlet, Francois; et al.
Abstract: Purpose: To evaluate feasibility and outcomes of minimally invasive surgery (MIS) in Wilms tumor (WT). Methods: International multicenter review of MIS total nephrectomies for WT between 2006 and 2018. Medical records of confirmed WT were retrospectively assessed for demographic, imaging, treatment, pathology, and oncological outcome data. Results: Fifty patients, with a median age of 38 months (6‐181), were included in 10 centers. All patients received neoadjuvant chemotherapy, as per SIOP protocol. Median tumor volume post‐chemotherapy was 673 mL (18‐3331), 16 tumors crossed the lateral border of the spine, and three crossed the midline. Six patients with tumors that crossed the lateral border of the spine (tumor volumes 1560 mL [299‐2480]) were converted to an open approach. There was no intraoperative tumor rupture. Overall, MIS was completed in 19% of the 195 nephrectomies for WT presenting during the study period. Tumor was stage I in 29, II in 16, and III in 5, and histology was reported as low in three, intermediate in 42, and high risk in five. Three patients had positive tumor margins. After a median follow‐up of 34 months (2‐138), there were two local recurrences (both stage I, intermediate risk, 7 and 9 months after surgery) and one metastatic relapse (stage III, high risk, four months after surgery). The three‐year event‐free survival was 94%. Conclusion: MIS is feasible in 20% of WT, with oncological outcomes comparable with open surgery, no intraoperative rupture, and a low rate of local relapse. Ongoing surveillance is, however, needed to evaluate this technique as it becomes widespread.